The Effect of H-PBL to Improving Student’s HOTS and ICT Skills in Physics Learning - Akhmad Jufriadi; Hena Dian Ayu; Riski Endah Setyawati (Universitas Muhammadiyah Purworejo, 2023)
This study aimed to analyze the effect of H-PBL to stimulating students HOTS and ICT skills. The model of H-PBL was a combination of online and direct learning. Direct learning was conducted by PBL. During online learning, the students conducted discussion through schoology applications that aimed to increase the ICT skills. The research design in this study was quantitative research with quasi-experimental type, the population that used in this study was students in 1st semester of pattern 6 in State Junior High School 5 Malang, while the sample in this study was 1 experimental class that used learning model of H-PBL and 1 control class that used learning model of PBL. The hypothesis was analyzed using the MANOVA test. The effectiveness of H-PBL learning could be known according to the improvement of learning result before and after using the H-PBL learning model and also could be known by differentiating the learning result of classes which used learning model of H-PBL dan PBL. The result of this study shown that the use of the learning model of H-PBL was proven effective in stimulating HOTS and ICT skills of students in energy materials. The analysis of this study obtained that the score of HOTS in the experimental class was 131.1 and for control class was 99.2, and the score of ICT skills in the experimental class was 18.7 while for control class was 17.8. The result shows H-PBL has effective to stimulated the student HOTS and ICT skill in Physics learning.